A promising biomarker to distinguish benign and malignant renal tumors: ELABELA - Artas, G.; Kuloglu, T.; Dagli, A. F.; Ugur, K.; Yardim, M.; Aydin, S.; Kocdor, H. (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this study was to investigate ELABELA (ELA) expression in benign and malignant renal tissues and expression differences in different nuclear grades of clear cell carcinomas. Materials and Methods: Patients that underwent surgery due to renal masses between the years of 2007 and 2017 were used. Control renal tissues (n = 23), papillary RCC (n = 23), clear cell RCC (CcRCC) [Fuhrman Grade1 (n = 23), Fuhrman Grade2 (n = 23), Fuhrman Grade3 (n = 23), Fuhrman Grade4 (n = 23)], and chromophobe RCC (n = 23) were included to the study. The Independent samples t-test was used for 2-point intergroup assessments and the one-way analysis of variance and posthoctukey test was used for the others. Values of P < 0.05 were considered statistically significant. Results: ELA immunoreactivity was observed in proximal and distal tubules in the kidney, but not in glomeruli in control tissues. When compared with control kidney tissue, a statistically significant increase was observed in ELA immunoreactivity in renal oncocytoma. In the chromophobe RCC, ELA immunoreactivity was significantly lower than control kidney tissue, whereas papillary RCC did not show ELA immunoreactivity. However, compared with control kidney tissue, ELA immunoreactivity was not observed in Fuhrman Grade 1 and Grade 2 CcRCC. Also, there was a significant decrease at Fuhrman Grade 3 and Grade 4 CcRCC compared with control kidney tissues. In the statistical analysis of ELA immunoreactivity among the Fuhrman nuclear grades of CcRCCs, The ELA immunoreactivity was higher at Grade 4 CcRCC than Grade 1, Grade 2, and Grade 3. Conclusion: ELA is a usefull molecule to differentiate benign and malign renal tumors. But further broad and comprehensive studies are needed to investigate cellular and molecular mechanisms of ELAs on malign transformation.
Keywords: ELABELA; immunohistochemistry; oncocytoma; renal cell carcinoma